ORGANIZATIONAL CHANGE: THE CASE OF THE NEW YORK POLICE DEPARTMENT - Yuksel, Yusuf (European Scientific Journal, ESJ, 2015)
This article analyzed the change at the New York Police Department (NYPD) after the appointment of William Bratton as police commissioner of the NYPD. It specifically argues the steps William Bratton took to effect a change and demonstrate elements of an effective change management process including the leader’s role in driving that change. This article demonstrated how five phases of change implemented in the NYPD. These phases are 1) defining goals and future state 2) creating an environment for change 3) planning the change 4) executing and improving and 5) integrating and sustaining change. In the discussion part, this article discussed how this model and the tactics can be adapted to manage the change of other police organizations, mainly İstanbul Police Department which is comparable to the NYPD in many respects. The implication of this paper is that it is possible to change the police and police organizations to serve in a way that responds the needs of changing society. The prior thing is a strong desire and increased understanding of change process.